Pattern Recognition Proteins: First Line of Defense Against Coronaviruses - Labarrere, Carlos A.; Kassab, Ghassan S. (Frontiers in Immunology, 2021)
The rapid outbreak of COVID-19 caused by the novel coronavirus SARS-CoV-2 in Wuhan, China, has become a worldwide pandemic affecting almost 204 million people and causing more than 4.3 million deaths as of August 11 2021. This pandemic has placed a substantial burden on the global healthcare system and the global economy. Availability of novel prophylactic and therapeutic approaches are crucially needed to prevent development of severe disease leading to major complications both acutely and chronically. The success in fighting this virus results from three main achievements: (a) Direct killing of the SARS-CoV-2 virus; (b) Development of a specific vaccine, and (c) Enhancement of the host’s immune system. A fundamental necessity to win the battle against the virus involves a better understanding of the host’s innate and adaptive immune response to the virus. Although the role of the adaptive immune response is directly involved in the generation of a vaccine, the role of innate immunity on RNA viruses in general, and coronaviruses in particular, is mostly unknown. In this review, we will consider the structure of RNA viruses, mainly coronaviruses, and their capacity to affect the lungs and the cardiovascular system. We will also consider the effects of the pattern recognition protein (PRP) trident composed by (a) Surfactant proteins A and D, mannose-binding lectin (MBL) and complement component 1q (C1q), (b) C-reactive protein, and (c) Innate and adaptive IgM antibodies, upon clearance of viral particles and apoptotic cells in lungs and atherosclerotic lesions. We emphasize on the role of pattern recognition protein immune therapies as a combination treatment to prevent development of severe respiratory syndrome and to reduce pulmonary and cardiovascular complications in patients with SARS-CoV-2 and summarize the need of a combined therapeutic approach that takes into account all aspects of immunity against SARS-CoV-2 virus and COVID-19 disease to allow mankind to beat this pandemic killer.